Real-Time Ventricular Volume Measured Using the Intracardiac Electromyogram. Issue 12 (22nd April 2021) - Schmid Daners, Marianne; Hall, Sophie; Sündermann, Simon; Cesarovic, Nikola; Kron, Mareike; Falk, Volkmar; Starck, Christoph; Meboldt, Mirko; Dual, Seraina A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Left ventricular end-diastolic volume (EDV) is an important parameter for monitoring patients with left ventricular assist devices (LVADs) and might be useful for automatic LVAD work adaptation. However, continuous information on the EDV is unavailable to date. The depolarization amplitude (DA) of the noncontact intracardiac electromyogram (iEMG) is physically related to the EDV. Here, we show how a left ventricular (LV) volume sensor based on the iEMG might provide beat-wise EDV estimates. The study was performed in six pigs while undergoing a series of controlled changes in hemodynamic states. The LV volume sensor consisted of four conventional pacemaker electrodes measuring the far-field iEMG inside the LV blood pool, using a novel unipolar amplifier. Simultaneously, noninvasive measurements of EDV and hematocrit were recorded. The proposed EDV predictor was tested for statistical significance using a mixed-effect model and associated confidence intervals. A statistically significant ( p = 3e–07) negative correlation was confirmed between the DA of the iEMG and the EDV as measured by electric impedance at a slope of –0.069 (–0.089, –0.049) mV/mL. The DA was slightly decreased by increased hematocrit ( p = 0.039) and moderately decreased with the opening of the thorax ( p = 0.003). The DA of the iEMG proved to be a significant, independent predictor of EDV. The proposed LV volume sensor is simple to integrate into the inflow cannula of an LVAD and thus has the potential to inform the clinician about the state of LV volume in real time and to automatically control the LVAD.